2019
DOI: 10.37358/rc.19.1.6852
|View full text |Cite
|
Sign up to set email alerts
|

Early Predictive Biochemical, Electrocardiographic and Echocardiographic Markers for Cardiac Damage in Patients with Pulmonic Silicosis

Abstract: The aim of this study was to identify correlations between electrocardiographic and echocardiographic changes in patients with silicosis prior to the occurrence of chronic pulmonary heart disease. We conducted a prospective, descriptive, analytical study, in which we included a group of 67 patients consecutively admitted to the Health Promotion and Occupational Medicine Clinic between December 2016 and January 2018, aged 47 to 78 years.There was a biochemical and electrocardiographic evaluation for each patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The results were comparable to those obtained in similar studies that concluded that almost 50% of invasive mammary carcinomas have both receptors positive whilst 25% are lacking in them [8][9][10][11][12]. The ER+/PR-phenotype represents a distinct group because it usually is accompanied by high clinical and biological aggressiveness and have the least satisfactory response to hormone therapy in comparison to other phenotypes [13][14][15][16].…”
Section: Resultssupporting
confidence: 83%
“…The results were comparable to those obtained in similar studies that concluded that almost 50% of invasive mammary carcinomas have both receptors positive whilst 25% are lacking in them [8][9][10][11][12]. The ER+/PR-phenotype represents a distinct group because it usually is accompanied by high clinical and biological aggressiveness and have the least satisfactory response to hormone therapy in comparison to other phenotypes [13][14][15][16].…”
Section: Resultssupporting
confidence: 83%
“…Our study included 305 patients with NSTEMI whose mean age was 70.62 ± 11.05 years CI 95% (69.28 -71.77) confirming the presence of non-ST-segment elevation myocardial infarction at older age [7][8][9][10][11] being more than 5 years old for women (73.36 ± 10.05 years) than for males (68.3 ± 11.32 years).…”
Section: Resultsmentioning
confidence: 88%
“…Echocardiography represents the imaging method of choice for assessing ventricular function in patients with clinical cardiac disease [1][2][3][4][5][6]. The multiple advantages are: echocardiography in emergency conditions, at hemodynamically unstable patients, it has good accuracy and is noninvasive and provides decisive information for diagnosis, risk stratification, therapeutic decision and follow-up of treatment effects.…”
mentioning
confidence: 99%